Symmetric semi-classical orthogonal polynomials of class one on q-quadratic lattices - Rebocho, M. N. (2020)
In this paper we study discrete semi-classical orthogonal polynomials on non-uniform lattices. In the symmetric class one case we give a closed form expression for the recurrence coefficients of orthogonal polynomials.